Modeling an Integrated Network for Remote Patient Monitoring, Based on the Internet of Things for a More Preventive and Predictive Health System in West Africa - AHOUANDJINOU, Mêtowanou Hérobert; MEDENOU, DATON; PECCHIA, Léandro; HOUESSOUVO, C. Roland; JOSSOU, Thierry Rock (My University, 2020)
Background: As a result of globalization it is important to examine health systems organization in Africa to highlight the failures and propose possible solutions in terms of patient care. Objective: Modeling was based on the Internet of Things (IoT) an Integrated Network for Monitoring Patient Data in West African Health Systems. Methodology: To achieve the objective three steps were followed. (1) Identification of the different characteristics of IoT-based health surveillance systems, Wireless Body Area Network (WBAN) systems, and the physiological parameters that are monitor-able on a patient. (2) The modeling of the architecture of West African health systems in the form of a cloud of technocenters. (3) Cross analysis between different IoT technologies, characteristics, and identification of any functional requirements. All this was based on wireless medical sensor networks in the WBAN systems. Result: This work has been used to model health systems in Africa as a remote monitoring network for patients. Conclusion: The implementation of this model of monitoring networks will be a tool to support large-scale decision-making for health systems in Africa. It will enable an information database for the West African health system.
Keywords: Modeling; Integrated Network; Internet of Things; health system; Technocentre.